История нищенства, кабачества и кликушества на Руси - Прыжов Иван Гаврилович (Русский дом, 1997)
Экземпляры: РБ (20231009) / Инвентарный номер: 66572 / Цена: 5.00 / Авт.знак: П85 / ГРНТИ: 03 / ББК: 63.5